(Des) Caminhos da adoção: a devolução de crianças e de adolescentes em famílias adotivas - Goes, Alberta Emília Dolores de (2014)
This thesis aims to understand what are the factors that lead to the return suitors adoption of children and adolescents under their responsibility, still in stage of living. The study originated from the everyday concerns of professional practice partner in the legal area. The work is divided into two parts. At first, we present a contextualization of the history of exposure and abandonment of children and the development of public policies that protect children and youth in Brazil, from the time of colonial Brazil until today. For this, we rely primarily on studies of the authors: Irene Rizzini, Maria Luíza Marcílio , Mary Del Priore, Myrian Veras Baptista, among others . We did a brief history of the adoption of children and adolescents, with the particularities of this issue in the Brazilian context, addressing their different conceptions, its historical and legal frameworks. We also highlight the reflection about who are the ' natural ' or ' biological ' children who are referred to the adoption families. Discussed in this direction that place the ' family of origin ' of the child occupies the stage of adoption, ie, they deliver, abandon or suffer state intervention? Also present some ideas about what comes to the adoption of children and adolescents and its various dimensions. And, from a comparative reflection, we discuss the changes on the processes of adoption of children and adolescents, occurring in the ACE from Law 12,010. The paper addresses the historical trajectory of insertion and retention of professional social work in the legal and social area for the development of this route we rely mainly on studies of the authors Eunice Teresa Fávero and Silvia Alapanian . Also treat the professional duties and responsibilities in this area of professional practice and processuality adoption. The second part of this work is composed of the methodological aspects used and the presentation of results. This is a qualitative research that had as subject the professional social service and psychology who work in the judiciary and an adoptive family. We also present the study of a particular case from the documentary analysis of a situation of return. About the adoptive filiation there are many myths and prejudices. In capitalist sociability, we have an adult-centered culture that contributes to the paradigm that adoption is ' still ' available to applicants , and in these cases it is not seen as a right of children and adolescents have a family , showing numerous challenges for which are seen as ' subject ' and ' citizens ' rights